The Mindanao Conflict: Efforts for Building Peace through Development. (2nd July 2016) - Ochiai, Naoyuki
Abstract : In its 2003 Official Development Assistance Charter (ODA Charter), the Japanese government made peace-building one of its areas of focus. Since then, the government and Japan International Cooperation Agency (JICA) have been active in organizing and implementing peace-building support projects in the Middle East, Africa, and Asia. One of the government's initiatives is a peacebuilding project in Mindanao, the Philippines, an effort that represents a break from the traditional mold: the development support efforts started contributing to the peace process before the signing of any peace agreement took place. This article examines how the development support initiatives by the Japanese government and JICA have contributed to the peace process in Mindanao from 2003 to 2016. Despite the unfamiliarity and uncertainty clouding the initial stages of the project, the development support efforts by the Japanese government and JICA are considered to have played a substantial role in paving the way toward the signing of the Comprehensive Agreement on Bangsamoro in March 2014.